Drug Use in Metropolitan America. - Bray, Dr. Robert M. M. (SAGE Publications, 1998)
This book describes, relates and integrates findings from a study of the Washington DC metropolitan area that looked at the nature and extent of drug use in a single urban setting. The research strategy involved focusing particularly on groups which have been traditionally underrepresented in household populations. The book serves as a methodological primer on how to undertake a study such as this. It places these findings in the larger context of the national drug abuse problem, as well as related social ills such as crime and homelessness. A concluding chapter looks squarely at some of the i.